2012
DOI: 10.1007/s11695-012-0641-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight in Children of Obese Patients: a Dietary Overview

Abstract: There is probably a significantly higher prevalence of obesity among children of morbidly obese parents when compared to the general child population. Since the familial aggregation of NCDs was absolute, these results point to the need for careful evaluation when dealing with children. However, further studies with a larger number of individuals are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(17 reference statements)
0
6
0
1
Order By: Relevance
“…El riesgo de obesidad infantil se multiplica por 4 si un padre es obeso y por 8 si ambos padres lo son. Se ha visto que la distribución de la grasa es idéntica de padres a hijos, con lo cual se puede decir que el genotipo influye en esta relación, Dicha relación se confirmó cuando se estudiaron a niños adoptados y gemelos univitelinos y bivitelinos en donde la distribución de grasa que presentaban tenía mayor relación con la carga genética que con la convivencia diaria (Pufal, 2012). Es por ello la necesidad de una máxima divulgación de las buenas prácticas alimentarias y sus consecuencias, así como el saber la clasificación de sobrepeso y obesidad de acuerdo a cada etapa de la vida.…”
Section: Obesidad Infantilunclassified
“…El riesgo de obesidad infantil se multiplica por 4 si un padre es obeso y por 8 si ambos padres lo son. Se ha visto que la distribución de la grasa es idéntica de padres a hijos, con lo cual se puede decir que el genotipo influye en esta relación, Dicha relación se confirmó cuando se estudiaron a niños adoptados y gemelos univitelinos y bivitelinos en donde la distribución de grasa que presentaban tenía mayor relación con la carga genética que con la convivencia diaria (Pufal, 2012). Es por ello la necesidad de una máxima divulgación de las buenas prácticas alimentarias y sus consecuencias, así como el saber la clasificación de sobrepeso y obesidad de acuerdo a cada etapa de la vida.…”
Section: Obesidad Infantilunclassified
“…With respect to sodium intake, increased acculturation was found to be associated with its increased consumption [11,41,44]. Behaviors associated with sodium consumption include eatingaway-from-home, consumption of meals at fast-food outlets and consumption of salty snacks [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Hands et al, 2011;Pufal et al, 2012) have associated E-intake behavior and S-behavior with childhood obesity. Therefore, we hypothesized that scores for the ERB-C scale should be higher among overweight or obese children than among underweight or normal-weight children.…”
Section: Known-group Validitymentioning
confidence: 99%
“…Researchers have confirmed that fried foods, greasy and starchy foods, snacks, and sweetened beverages are the most common types of food that contribute to excessive energy intake (Ansa, Anah, & Ndifon, 2008;Department of Health and Aging, 2010;Receveur, Morou, Gray-Donald, & Macaulay, 2008). Obese children typically have a higher percentage intake of lipid calories and consume more sweetened beverages than their nonobese peers (Collison et al, 2010;Pufal et al, 2012). In addition, sedentary behavior (S-behavior) is an important contributor to energy accumulation.…”
Section: Introductionmentioning
confidence: 99%